2002
DOI: 10.1029/2001wr000522
|View full text |Cite
|
Sign up to set email alerts
|

Multiscaling pulse representation of temporal rainfall

Abstract: [1] We develop a pulse-based representation of temporal rainfall with multifractal properties in the small-scale limit. The representation combines a traditional model for the exterior process at the synoptic scale with a novel hierarchical pulse model for the event interiors. For validation we apply the model to a temporal rainfall record from Florence, Italy. Although the model has only six parameters (four for the exterior process and two for the event interiors), it accurately reproduces a wide range of em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
67
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(69 citation statements)
references
References 34 publications
2
67
0
Order By: Relevance
“…Due to the occurrence of a 4-month dry period in Mediterranean semi-arid areas, it is not surprising to observe a particular behaviour concerning the length of the saturation period. We obtained a beginning for the saturation period after 113 d. Considering Table 1, Olsson (1993) used rainfall data collected at Lund (Sweden), Hubert and Carbonnel (1989) data obtained in Ouagadougou (Burkina Faso), Lavergnat and Golé (1998) data from Palaiseau (France), Schmitt et al (1998) (Belgium) and Veneziano and Iacobellis (2002) data collected at Florence (Italy), and in each case the scale break for saturation is observed to be a few days, respectively 7, 21, 7, 3.5 and 3.5 d, which attests to the importance of the length of the saturation regime as well as the relative homogeneity of the rain support throughout the year. In other words, the length of the saturation period is very particular to the area considered.…”
Section: With the Sensor Detection Thresholdmentioning
confidence: 99%
“…Due to the occurrence of a 4-month dry period in Mediterranean semi-arid areas, it is not surprising to observe a particular behaviour concerning the length of the saturation period. We obtained a beginning for the saturation period after 113 d. Considering Table 1, Olsson (1993) used rainfall data collected at Lund (Sweden), Hubert and Carbonnel (1989) data obtained in Ouagadougou (Burkina Faso), Lavergnat and Golé (1998) data from Palaiseau (France), Schmitt et al (1998) (Belgium) and Veneziano and Iacobellis (2002) data collected at Florence (Italy), and in each case the scale break for saturation is observed to be a few days, respectively 7, 21, 7, 3.5 and 3.5 d, which attests to the importance of the length of the saturation regime as well as the relative homogeneity of the rain support throughout the year. In other words, the length of the saturation period is very particular to the area considered.…”
Section: With the Sensor Detection Thresholdmentioning
confidence: 99%
“…Cascade weights have been found to be dependent on scale (Veneziano et al, 1996;Menabde et al, 1997;Menabde and Sivapalan, 2000;Molnar and Burlando, 2005;Paulson and Baxter, 2007), on covariates such as large-scale rainfall intensity (Over andGupta, 1994, 1996;Deidda, 2000;Molnar and Burlando, 2005), and on the interval class, i.e. intervals at the beginning, middle, or end of a rainfall event (Olsson, 1998;Olsson and Berndtsson, 1998;Güntner et al, 2001;Veneziano and Iacobellis, 2002). Veneziano et al (2006) have explored the dependence of the cascade weights on rainfall intensity and cascade level, assuming the so-called discrete canonical logstable model, which accounts for zero rainfall (hereinafter, also denoted as lacunarity) thanks to a thresholding procedure, and the beta-logstable (BLS) model (described in Sect.…”
Section: Introductionmentioning
confidence: 99%
“…combine a stochastic rainfall forcing with a reliable representation of physical dynamics affecting basin response. In particular, Fiorentino et al (2007) used a distributed hydrological model (Manfreda et al, 2005) in cascade with a rainfall generator with multifractal properties (Veneziano and Iacobellis, 2002). They investigated the role of climate, soil and vegetation in runoff generation during extreme events and concluded that runoff source areas are mainly affected by pedologic features in arid basins, while a geomorphologic control prevails in humid basins.…”
Section: Introductionmentioning
confidence: 99%